PENERAPAN GRI-G4 SEBAGAI PEDOMAN BAKU SISTEM PELAPORAN BERKELANJUTAN BAGI PERUSAHAAN DI INDONESIA - Silvana Faiqoh; Mohammad Iqbal As'ad Mauludy (Universitas Jember, 2018)
The discussion is aimed at reviewing the seriousness of the company, especially in allocating, reporting, and disclose the costs that associated with activities that cause the decrease of the environmental function that on a certain point, it will result in damage to the ecosystem environment. Understanding the company in maintaining the balance of the environment i.e. related application of green accounting. The company’s accountability was aimed for the stakeholders, so they need a standard to show that the company is serious in making the application of responsibility towards society and the environment. This research is a descriptive qualitative methods research. The results obtained as an attempt of creating the company's seriousness in maintaining environmental sustainability despite increased profits for the company i.e. the need for standard setting the right business sustainability reporting, with financial and non financial parameters, where through the new standards so that the nature of the disclosure of environmental cost will become mandatory, and has deleted the voluntary disclosure. The second step i.e. obligate the company in making appropriate sustainability reporting framework that applies according to which hinted at the standard, in this case refers to the Global Reporting Initiative (GRI)-G4.